Husband's Support with the Anxiety Level of Trimester III Pregnant Women in the Era of Adaptation to the Covid-19 Pandemic - Nurdiana; Nurlina Nurlina; Nurbiah Eka Susanty (Jurnal Ilmiah Kesehatan (JIKA), 2023)
Physical and mental variations during pregnancy will quite often cause pressure. The aim of this study was to decide the connection between a spouse's help and the nervousness level of third-trimester pregnant ladies during the time of transformation during the Coronavirus pandemic. Cross-sectional analytic surveys were used in this kind of study. The number of inhabitants in this study was all pregnant ladies who completed Antenatal Consideration (ANC) at the Manuju Wellbeing Center, Manuju Area, Gowa Rule for the period August 2022 upwards of 43 individuals. The example was third-trimester pregnant ladies at the Manuju wellbeing focus utilizing the purposive testing procedure utilizing the Slovin equation, comprising 35 subjects. The chi-square analysis method was used in conjunction with the Hamilton Anxiety Rating Scale (HARS) in the instrument. The results of the Chi-Square statistical test, which yielded a p-value of p-value=0,02 and a correlation coefficient of 0,691, demonstrated that there was a significant correlation between the level of anxiety experienced by pregnant women in the third trimester and the husband's support during the period of adaptation to the Covid-19 pandemic. So, one can conclude that the husband's support for pregnant women is stronger the more anxious they are.